OSTEOPLASTIC THORACOMYOPLASTY IN THE TREATMENT OF PATIENTS WITH MULTIDRUG-RESISTANT DESTRUCTIVE PULMONARY TUBERCULOUS - K. T. Istamov; R. G. Gaipov; A. S. Kadyrov; M. M. Mamytova (Туберкулез и болезни лёгких)
The paper gives indications for remedial osteoplastic thoracomyoplasty, its advances and techniques. It shows the specific features of modified thoracomyoplasty. The results of this surgical intervention are analyzed in 98 patients from the Lung Surgery Department of the National Center of Phthisiology. The clinical efficiency of the operation was noted in 92.8% of the patients.